Design elements for gender-responsive breeding: Starting points and unresolved issues - Ashby, Jacqueline A. (CGIAR Consortium, 2017)
Presented by Jacqueline Ashby on 21 September 2017, as part of the webinar 'Design elements for gender-responsive breeding'. The webinar was co-organized by the CGIAR Collaborative Platform for Gender Research and the CGIAR Research Program on Roots, Tubers and Bananas.